PENGARUH KESADARAN WAJIB PAJAK DAN PENERAPAN E-FILING TERHADAP KEPATUHAN WAJIB PAJAK (STUDI PADA UMKM YANG TERDAFTAR DI KPP PRATAMA CANDISARI SEMARANG) - Patricia Mauly Bertha Situmorang; Saryadi Saryadi (Universitas Diponegoro, 2017)
Tax has a large contribution of the national income because most of the nation’s activities financed by tax revenue. Income tax is the largest tax revenue compared to other tax types. Although income tax is one of the highest tax revenue, there are still many tax subjects who are not yet paying tax. In order to encourage people to pay tax, various efforts such as online tax service are supported with regulation of Direktur Jendral Pajak Nomor PER-41 / PJ / 2015.The purpose of this study is to determine the effect of taxpayer consciousness, and implementation of e-filing to taxpayer compliance. The hypothesis in this research is the existence of positive and significant influence between the variable of taxpayers conciousness and the implementation of e-filing affect the SMEs taxpayer compliance.The method in this research is quantitative with explanatory research type. Data analysis technique is validity test, reliability test, coefficient of correlation, coefficient of determination, simple linear regression, multiple linear regression, t test and F test using SPSS (Statistical Program for Social Science) program for Windows version 16.00.The results showed that the variable taxpayer consciousness has a positive and significant effect on taxpayer compliance, the variable implementation of e-filing has a positive and significant effect on taxpayer compliance, taxpayer awareness and implementation of e-filing have positive and significant effect to taxpayer compliance. Taxpayer compliance still needs to be improved so that in this research suggest to socialize the importance of the tax and training or workshop about the use of e-filing. This research is also expected as an input for the next researcher.